Ventajas y desventajas del leasing financiero en las pymes de Palmira (2020)
According to the Chamber of Commerce, in Palmira in 2017 SMEs represented 7% of the total of the 7,684 companies in the municipality. At some point in their activity, the lack of liquidity that SMEs go through is the origin of other major problems such as non-payment to their workers, the financial system and other obligations, as well as difficulties in accessing machinery, equipment and software to increase their productivity and be competitive in the market. One of the mechanisms they can access to solve this financial problem is leasing. In Colombia, according to Asobancaria the portfolio of SMEs in leasing between December 2018 and March 2019 decrease (-0,23 pp.). In Valle del Cauca (Romero, Melgarejo and Vera-Colina (2015)) 85% of SMEs are classified as failed, (illiquid), which may explain the decrease in this sector in Palmira. Leasing is a contract through which a lessor cedes the right to use a certain asset to a lessee, in exchange for the payment of rental income, for a specified time. Leasing has become relevant, especially for SMEs, since it offers many advantages, including the possibility of increasing investment levels when difficulties are encountered in accessing traditional lines of financing. With the leasing modality, companies have the possibility to modernize and renew their assets such as vehicles or technological equipment without incurring higher acquisition costs.